Impact on Extreme Rainfall and Flood Events during Boreal Summer Intraseasonal Oscillation (BSISO) in Aceh Province, Indonesia - Qalbi, Harisa Bilhaqqi; Abdullah, Faisal; Ismail, Nazli (UIR PRESS, 2024)
The Boreal Summer Intraseasonal Oscillation (BSISO) is intraseasonal climate variability in addition to the Madden-Julian Oscillation (MJO) that affects weather and climate in the Indo-Pacific region including the Province of Aceh. The impact of BSISO on extreme rainfall and flooding in Aceh needs to be investigated to enhance preparedness, mitigation, and adaptation strategies against its negative impacts. The datasets use in situ daily rainfall data from 5 BMKG stations in Aceh and the BSISO indices (BSISO1 and BSISO2) during the extended boreal summer (May–October) period 2001–2020, as well as flood event data in Aceh from 2008–2020. The results of this study show that rainfall in Aceh province is influenced by BSISO variability and has the potential to increase extreme rainfall and even cause flooding in some areas in Aceh, depending on the propagation path of BSISO. The frequency of extreme rainfall in Aceh during BSISO is identified using daily rainfall beyond the 95th percentile in each BSISO phase, which increases the probability of extreme rainfall in Aceh by around 20–100% during phases 1-3 in both BSISO1 and BSISO2. During BSISO1, the probability of flooding in phases 1-3 increased by up to 90%, and BSISO2 also increased the probability of flooding in phases 1-4 by up to 72%.